Bacteriophages as an Up-and-Coming Alternative to the Use of Sulfur Dioxide in Winemaking - Cordero-Bueso, Gustavo; Moraga, Javier; Ríos-Carrasco, María; Ruiz-Muñoz, Marina; Cantoral, Jesús Manuel (Frontiers in Microbiology, 2020)
Certain acetic and lactic acid bacteria are major causes of quality defects in musts and wines, giving rise to defects such as a “vinegary,” “sharp, like nail polish-remover” taste or preventing alcoholic and/or malolactic fermentation. Sulfur dioxide is the major tool currently used in the control of these bacteria in wine. The aim of this work was to isolate bacteriophages from musts and wine of different grape varieties that were able to eliminate lactic and acetic acid bacteria spoilages at the laboratory scale. Musts obtained from grape-berries of Vitis vinifera cv. Chardonnay and Moscatel and a red wine made with V. vinifera cv. Tintilla de Rota were used to isolate bacteriophages. Bacteriophages were obtained from each of the musts and the wine and belonged to the order Caudovirals and the family Tectivirals. They were isolated by classical virology methods and identified by electron microscopy. The host bacteria used in the study were lactic acid bacteria of the species Lactobacillus hilgardii, Lactobacillus plantarum, and Oenococcus oeni and the acetic bacteria Acetobacter aceti. A comparative study was performed by adding phage titrations and SO2 to musts and wines, which had been previously inoculated with bacteria, to study the effectiveness of bacteriophages against bacteria. The comparative study showed that some bacteriophages were as effective as sulfur dioxide at low concentrations.